The reason for the darkness of the night : Edgar Allan Poe and the forging of American science - Tresch, John, 1972- (Farrar, Straus and Giroux, 2021)
"A biography of Edgar Allan Poe with an emphasis on his engagement with the scientists and scientific discoveries of his era"--